1997
DOI: 10.1016/s0014-5793(97)00007-0
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of insulin‐stimulated phosphatidylinositol 3‐kinase activity by the β3‐adrenoceptor agonist CL316243 in rat adipocytes

Abstract: Insulin increased 2-deoxyglucose (2-DG) uptake via the translocation of glucose transporter (GLUT) 4 to the plasma membrane fraction in rat adipocytes. The stimulatory actions of insulin were accompanied by both an increase in the immunoreactive p85 subunit of phosphatidylinositol (PI) 3-kinase in the plasma membrane fractions and PI 3-kinase activation by tyrosine phosphorylation of the p85 subunit. The ß 3 -adrenoceptor agonist CL316243 (CL) suppressed all the insulin actions in adenosine deaminase (ADA)-tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 33 publications
2
13
0
Order By: Relevance
“…This suggests insulin receptor-independent and receptor-dependent cross-talking mechanisms. In agreement with this work, Ohsaka et al (28) have demonstrated that insulin-stimulated PI 3-kinase activity is suppressed by ␤ 3 -adrenergic stimulation in rat adipocytes via a direct cAMP-dependent mechanism. Furthermore, this decrease in PI 3-kinase activity is associated with a reduction in insulin-induced activation of Akt.…”
Section: Discussionsupporting
confidence: 85%
“…This suggests insulin receptor-independent and receptor-dependent cross-talking mechanisms. In agreement with this work, Ohsaka et al (28) have demonstrated that insulin-stimulated PI 3-kinase activity is suppressed by ␤ 3 -adrenergic stimulation in rat adipocytes via a direct cAMP-dependent mechanism. Furthermore, this decrease in PI 3-kinase activity is associated with a reduction in insulin-induced activation of Akt.…”
Section: Discussionsupporting
confidence: 85%
“…Although previous studies have reported only inhibitory effects of cAMP-elevating agents on lipid kinase activity, these studies were conducted in differentiated cells (1,48) or in cells where cAMP fails to stimulate mitogenesis (9,45,61). Our data indicating that both PI3K and Rac1 are required for cAMP-stimulated proliferation, together with the stimulatory effects of cAMP on Akt and membrane ruffling, strongly support the idea that cAMP stimulates PI3K activity.…”
Section: Discussionsupporting
confidence: 79%
“…For most growth factors shown to require PI3K activity, growth factor treatment stimulates lipid kinase activity. Although only inhibitory effects of cAMP on PI3K lipid kinase activity have been reported, these studies were performed in differentiated cells, i.e., adipocytes (48) and neutrophils (1), or in cells where cAMP fails to stimulate proliferation, such as bovine airway smooth muscle cells (61), B16 melanoma cells (9), and lymphoid cells (45). Whether cAMP requires PI3K activity in cells where it is a mitogen was examined here.…”
mentioning
confidence: 99%
“…It is not clear whether increased sympathetic nervous system activity, commonly found in insulin resistance syndrome (122), contributes to decreased insulin signaling. However, in brown adipocytes (Klein, J., and Kahn, C.R., unpublished data) and white adipocytes (123), stimulation of the β-adrenergic receptor decreases insulin-stimulated PI3-kinase activity. Desensitization of β-adrenergic receptors by isoproterenol increases insulin-stimulated glucose uptake in white adipocytes (124).…”
Section: Acquired Factorsmentioning
confidence: 96%